Applying the stimulus–organism–response model to social media-driven organic vegetable consumption among housewives in Malang City - Fithana Silma Ridani; Mofit Jamroni; Rizka Amalia (University of Islam Malang, 2026)
Sustainable food consumption has become increasingly important in promoting environmentally responsible household food choices, including organic vegetable consumption. Although social media is widely used to disseminate health and environmental information, few studies have examined how access to social media stimulates organic vegetable consumption by fostering environmental awareness among housewives in a local agribusiness context. This study fills this gap by applying the Stimulus–Organism–Response (SOR) model to explain participation in organic vegetable consumption among housewives in Malang City. A quantitative survey was conducted with 65 housewives who had purchased and consumed organic vegetables and actively used social media. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that social media access had a positive and significant effect on environmental awareness (β = 0.826; p < 0.001), environmental awareness significantly influenced organic vegetable consumption participation (β = 0.520; p < 0.001), and social media access directly affected consumption participation (β = 0.430; p < 0.001). Environmental awareness also mediated the relationship between social media access and participation in organic vegetable consumption. However, 60% of respondents purchased organic vegetables less than five times per month, indicating an awareness–behavior gap. These findings strengthen the SOR model in explaining sustainable consumption behavior and highlight the strategic role of digital communication in organic vegetable market development. The study suggests that organic farmers, retailers, and digital marketers should integrate consumer education, transparency in certification, and targeted social media campaigns to strengthen household participation in sustainable agribusiness.